Eusapia Palladino Anthologized - Alvarado, Carlos S. (Journal of Scientific Exploration, 2017)
This is an essay review of Eusapia Paladino: Materialisations and Intellergetic Phenomena in Physical Mediumship, compiled by Scott Dickerson (No publication place: Runabout, 2016. 286 pp. ISBN-13: 978-1530915859).